2015
DOI: 10.1002/2015gl064188
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric deposition—Another source of nutrients enhancing primary productivity in the eastern tropical Indian Ocean during positive Indian Ocean Dipole phases

Abstract: This study used in situ and multisensor satellite data and combinations of various primary productivity (PP) and surface nitrate models to assess the contributions of upwelling and atmospheric deposition to modulating PP in the eastern tropical Indian Ocean (ETIO) during positive phases of the Indian Ocean Dipole (+IOD). Surprisingly, atmospheric deposition of nutrients from wildfires accounted for a higher portion of enhanced PP during +IODs than wind‐driven nutrient upwelling. Substantial atmospheric nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In contrast, SST, tropical cyclones, and rainfall can explain more about the variance in annual BSi in the nIOD phase (Table 2). The result is consistent with the model evaluations in the eastern Indian Ocean between 1997 and 2009, which showed that the atmospheric deposition of nutrients from wildfire accounted for a higher proportion of MPP increase than that of wind-driven nutrient upwelling in pIOD phases 33 .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, SST, tropical cyclones, and rainfall can explain more about the variance in annual BSi in the nIOD phase (Table 2). The result is consistent with the model evaluations in the eastern Indian Ocean between 1997 and 2009, which showed that the atmospheric deposition of nutrients from wildfire accounted for a higher proportion of MPP increase than that of wind-driven nutrient upwelling in pIOD phases 33 .…”
Section: Discussionsupporting
confidence: 90%
“…The patchiness of the plankton and their seasonal and interannual variations can cause large overall errors as well. A recent study by Siswanto [] showed that atmospheric deposition of nutrients from wildfires accounted for a higher portion of enhanced primary production during positive phases of the Indian Ocean Dipole than did wind‐driven nutrient upwelling in the eastern tropical Indian Ocean. We suggest that the contribution of atmospheric deposition to new production in the Oman upwelling regions, where mineral dust aerosols are significantly high, is larger than 3% by an order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…The tropical Indian Ocean forms the major part of the largest warm pool on the earth, and its interaction with the monsoon plays an important role in shaping complex circulation systems on both regional and global scales (Wang, Xie, & Carton, ). Furthermore, the variability of nutrients, biomass, and primary production in the Indian Ocean induced by changes in physical forces have been investigated by a number of studies (McClanahan, Maina, Graham, & Jones, ; Roxy et al., ; Siswanto, ), which usually showed that the variability in phytoplankton standing stocks and primary production are closely related to the circulations and water masses. Although the Indian Ocean is considered as one of the largest oligotrophic areas, it has received far less attention than other oceans, particularly in terms of the size and biomass of picophytoplankton.…”
Section: Introductionmentioning
confidence: 99%